528 Sexual dimorphism in myeloid-derived suppressor cells promote GBM progression in females via IL-1b. (9th November 2020) - Bayik, Defne; Zhou, Yadi; Park, Chihyun; Hong, Chngjin; Silver, Danielle; Watson, Dionysios; Lo, Alice; Hwang, Tae Hyun; Cheng, Feixiong; Sims, Peter; Iavarone, Antonio; Lathia, Justin
Abstract : Background: A potently immunosuppressive tumor microenvironment facilitates progression of glioblastoma (GBM). Immunotherapies have had variable success in improving the outcome of GBM patients, suggesting that there is a need to gain insight into the mechanisms of immunosuppression. Our findings indicated that proliferating monocytic MDSCs (mMDSCs) accumulate in tumors of male mice and patients, while female tumor-bearing mice had an increase in circulating granulocytic MDSC (gMDSC) frequency, and a high gMDSC gene signature correlated with worse outcome of female patients. Methods: To investigate the basis and prognostic value of sex differences in MDSC profile, we analyzed the role of sex hormones, determined gene expression signatures of MDSCs and preclinically tested the therapeutic benefit of candidate drugs predicted to be effective against individual MDSC subsets. Results: In line with the differential MDSC accumulation pattern, targeting the systemic gMDSCs with the anti-Ly6G neutralizing antibody extended the lifespan of female mice without affecting males. These differences were not driven by sex steroids, as castration or ovariectomy failed to alter MDSC subset accumulation patterns in GBM-bearing mice. Drug-prediction algorithms using the differential MDSC gene expression profiles predicted IL-1 inhibitors are effective against gMDSCs. Correspondingly, IL-1β was highly expressed in female but not male gMDSCs. Single-cell sequencing revealed that circulating but not tumor-infiltrating gMDSCs were the primary source of IL-1β and that its neutralization provided a female-specific survival advantage by reducing circulating gMDSCs. This was accompanied by declines in tumor infiltration of microglia, microglia activation status and tumor cell proliferation. In vitro, IL-1β inhibition reduced viability and expression of activation markers by primary microglia. Conclusions: These findings highlight a novel peripheral gMDSC-microglia IL-1β mediated communication axis in female GBM and indicate expression differences in MDSC subsets can be leveraged for improved immunotherapy efficacy in a sex-specific, precision medicine strategy.